Perbedaan Pertumbuhan dan Perkembangan Anak Usia Toddler (1-3 Tahun) pada Ibu Bekerja dan Ibu Tidak Bekerja di Posyandu Desa Sukamanah dan Karang Anyar - Maryani, Maryani; Muriah, Muriah; Nuraeni, Reni (Universitas Malahayati, 2025)
ABSTRACT During the toddler years, it will greatly influence and determine the child's subsequent growth and development, to maintain the continuity of life while improving the quality of life of the child in order to achieve optimal growth and development both physically, mentally, emotionally and socially, therefore during the toddler years it is very important to pay attention so that toddlers do not experience delays in growth and development. To determine the differences in growth and development of toddler age children among working mothers in Sukamanah Village and Karang Anyar Village in 2024. This type of research is observational analytic, with a cross sectional design, which is a study to study the correlation between risk factors (independent) in this study